2012
DOI: 10.1111/j.1752-699x.2012.00294.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of mold sensitization and humidity upon allergic asthma

Abstract: Mold sensitization is highly associated with more severe asthma, while humidity is more of an exacerbating factor in patients with allergic asthma as compared with allergic rhinitis alone. Further delineation between mold sensitization and humidity is needed to determine whether these are independent factors in asthma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 52 publications
2
19
0
1
Order By: Relevance
“…Interestingly, there have been no differences in controlled asthma between seasonal or perennial allergens. When comparing perennial allergens, Alternaria ‐allergic patients with asthma show a worse level of controlled disease (based on GEMA guidelines) in concordance with previous reports in adults . In fact, fungal sensitization has been associated with increased asthma morbidity and mortality, including higher rates of hospitalization .…”
Section: Discussionsupporting
confidence: 82%
“…Interestingly, there have been no differences in controlled asthma between seasonal or perennial allergens. When comparing perennial allergens, Alternaria ‐allergic patients with asthma show a worse level of controlled disease (based on GEMA guidelines) in concordance with previous reports in adults . In fact, fungal sensitization has been associated with increased asthma morbidity and mortality, including higher rates of hospitalization .…”
Section: Discussionsupporting
confidence: 82%
“…Conversely, a Japanese study demonstrated an association between low relative humidity and hospital admissions for paediatric asthma admissions. Indirect effects of humidity on respiratory disease include the role of moist indoor environments in promoting the growth of mold and the reproduction of mites (Hayes et al, 2013;Richardson et al, 2005;Williamson et al, 1997) and the effects of humidity on pollen dispersal and pollen-related allergens (Bartkova-Scevkova, 2003). In a series of controlled climate chamber studies on exercise performance (Eschenbacher et al, 1992), asthma patients exhibited significantly greater bronchoconstriction after exercise than non-asthmatic subjects as RH decreased.…”
Section: Humidity and Pulmonary Diseasementioning
confidence: 99%
“…The provision of evidence linking damp indoor environments and fungal diversity to adverse health outcomes has practical implications by informing future health interventions. For example, these could be used to target high‐risk populations such as those sensitized to specific fungi that are more likely to suffer from severe asthma , households with infants, and other important fungal‐related health problems. These may include life threatening infections, allergic bronchopulmonary aspergillosis, aspergilloma (fungus ball), invasive pulmonary aspergillosis, chronic necrotizing aspergillosis and allergic fungal rhinosinusitis , not reviewed here.…”
Section: Indoor Damp Fungi and Risk Of Asthmamentioning
confidence: 99%